2001
DOI: 10.1007/s11746-001-0280-5
|View full text |Cite
|
Sign up to set email alerts
|

Interesterification of tallow and sunflower oil

Abstract: The objective of this study was to manufacture a shortening using chemical interesterification (IT) of tallow-sunflower oil blends to replace fish oil in the present formulation, which is now in short supply in Chile. The significant variables of the IT process were obtained by 2 4-1 fractional factorial design. The proportion of tallow (T) in the blend, catalyst concentration, and reaction temperature had a significant effect on the melting point (mp) (P ≤ 0.05). IT of tallow and sunflower oil blends (90:10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 13 publications
9
41
0
1
Order By: Relevance
“…SFC is, in this sense, responsible for many product characteristics including general appearance, ease of packing, organoleptic properties, ease of spreading, and oil exudation. SFC can also be used to study the compatibility of fats by determining the changes in the percentage of solids at different fat proportions (RODRIGUEZ et al, 2001;NOOR LIDA;ALI, 1998). The texture of a SL can be measured via cone penetrometry using an INSTRON™ testing machine or a texture analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…SFC is, in this sense, responsible for many product characteristics including general appearance, ease of packing, organoleptic properties, ease of spreading, and oil exudation. SFC can also be used to study the compatibility of fats by determining the changes in the percentage of solids at different fat proportions (RODRIGUEZ et al, 2001;NOOR LIDA;ALI, 1998). The texture of a SL can be measured via cone penetrometry using an INSTRON™ testing machine or a texture analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that blends formulated by mixing fully hydrogenated soybean oil with the commonly used nine vegetable oils in a ratio of 1:1 (wt/wt) were interesterified and resulted in speciality fats with no trans fatty acids [10]. Bakery shortenings were prepared from tallow and sunflower oil blends in various ratios by interesterification [11]. The trans fatty acid-free bakery shortenings were prepared from vegetable fats and oils by fractionation and blending [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…33,49,50 Nutricionalmente, esta reação promove benefícios quando comparada à hidrogenação, pois o processo de rearranjo dos ácidos graxos não altera sua isomeria ou seu grau de insaturação, 33 o que leva à geração de produtos com quantidade reduzida ou livre de isômeros trans e que podem possuir maiores concentrações de ácidos graxos poli-insaturados. 5 O uso da interesterificação é uma tendência que se apresenta como alternativa promissora na indústria de gorduras para alterar também propriedades de espalhabilidade, pois modifica substancialmente as propriedades físicas das gorduras.…”
Section: Modificação Bioquímica Da Gordura Do Leiteunclassified